Financial Deepening, Interest Rate Spread and Economic Growth: New Evidence from Sub-Sahara Africa - Jalloh, Mohamed; Guevera, Yao (International Journal of Business, Economics and Management, 2017)
This study examines the nexus between financial deepening, interest rate spread and economic growth using data from Sub-Sahara African (SSA) countries. A dynamic panel approach is employed in estimating the parameters of the specified equation using the Sargan test of over-identification restriction in assessing the validity of the instruments used in addressing potential endogeneity problems of the data. The results show that whilst financial deepening positively drives growth, interest rate spread adversely affect growth in countries studied. In terms of relative effects, the results indicate that enhancing financial deepening by10.0 percent induces economic growth on average by a margin of 4.2 percentage points. On the contrary, however, raising interest rate spread by 10.0 percent reduces growth on average by a margin of 3.6 percentage points in countries studied. Based on these findings, there is a strong need for the implementation of policies that promote financial deepening. In particular, there is a strong need for financial authorities supervising the activities of commercial banks to ensure low interest rate spreads with a view to promoting the efficiency of banks in effectively playing their financial intermediation role to boost economic growth for poverty reduction in SSA countries.